How does climate exacerbate root causes of conflict in Kenya? Climate Security Pathway Analysis - Dutta Gupta, Tanaya; Hassan, Gamal Mohamed; Abdi, Abdimajid Nunow; Madurga Lopez, Ignacio M.; Liebig, Theresa Ines; Santa Cruz, Leonardo Medina; Sax, Niklas; Läderach, Peter R.D.; Pacillo, Grazia (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2023)
This factsheet gives answers on how climate exacerbates root causes of conflict in Kenya, using A climate security pathway analysis. Two main impact pathways are identified: 1) Resource availability and access pathway; 2) Livelihood and food insecurity pathway. This publication is part of a factsheet series reporting on the findings of the CGIAR FOCUS Climate Security Observatory work in Africa (Kenya, Mali, Nigeria, Senegal, Sudan, Uganda, Zimbabwe). The research is centered around 5 questions: 1. How does climate exacerbate root causes of conflict? 2. Where are hotspots of climate insecurities ? 3.What is the underlying structure of the climate, conflict, and socio-economic system? 4. Are climate and security policies coherent and integrated? 5. Are policy makers aware of the climate security nexus?